Long-term survival after coronary bypass surgery. Comparison of various subsets of patients with general population. Issue 4 (April 1981) - Greene, D G; Bunnell, I L; Arani, D T; Schimert, G; Lajos, T Z; Lee, A B; Tandon, R N; Zimdahl, W T; Bozer, J M; Kohn, R M; Visco, J P; Dean, D C; et al.
Abstract : Life-table analysis consecutive cases of isolated coronary bypass surgery at the Buffalo Hospital between 1973 and 1977 showed an estimated survival of 94 per cent at five years, equal to that of an age- and sex-matched group of the US population. Subsets of these patients divided according to sex, age, number of vessels narrowed, number of segments grafted, history of myocardial infarction, ejection fraction, and presence of unstable angina have estimated survivals not statistically less in any of these subsets than that of matched cohorts of the general population.